Human trafficking in the Andean region: Socio-spatial dynamics in the Peruvian borders - Manuel Dammert Guardia; Lucia Dammert; Katherine Sarmiento (Íconos)
Human trafficking is an illegal activity that harms the dignity and freedom of thousands of people, many of them women; but which is still not a priority in public debates and about which there is still little information. This article explores the socio-spatial dynamics of human trafficking on the national borders of Peru, as a contribution to the study of the complex relationships that exist between criminal activity and territory. The analysis of human trafficking in the borders between Peru and Ecuador and between Peru and Bolivia during the period 2000-2014 is based on a hemerographic review, statistical information generated by government sources competent in the matter and secondary data produced by international organizations. The article argues that borders constitute a strategic site for human trafficking in four different ways: i) they allow the formation of circuits, stages and itineraries that: ii) facilitate the incorporation of this criminal activity as a part of local life iii) they increase the dangers and vulnerabilities of cross-border migration and iv) they reveal the systemic connections of this illegal market to global processes.